Pelatihan Microsoft Office dan Aplikasi Kerja pada Murid PKBM Bina Anak Nusantara - Hadiyani, Sherry; Adnans, Abdhy Aulia; Miranti, Alia; Fadillah, Adam; Purba, Akbarken; Naumi, Cindy Aprilia; Irvana, Eva (Jurnal Abdimas Multidisiplin, 2024)
Purpose: The purpose of the training is to improve computer usage skills and provide knowledge in the world of work in the community so that it can improve the wheels of the economy. Methodology: The methods used in this service are lectures, discussions, and practices from each stage of training on the use of Microsoft Office such as Microsoft Word, Microsoft Excel, and Microsoft Power Point, then the introduction and practice of using work applications. The work applications introduced were software applications such as LinkedIn, JobStreet, and KitaLulus. Results: As a result of this training, the participants were able to understand and enthusiastically participate in all activities. The trainees were able to complete practical tasks that had been given well. Limitations: The limitations of this community service need to increase the use of soft offices further, not only the basics, so that participants can further develop their ability to use soft offices. Contribution: This training can add to the skills of trainees in using Microsoft Office and introduce work applications so that they can later become provisions in the world of work. As long as it runs, this service has produced several outputs such as (1) submitted Scientific Journal articles, (2) mass media publications, (3) publication of activity videos, (4) increased competitiveness, (5) increased application of science and technology, and (6) Intellectual Property Rights (HAKI) from cinematography.